Role of Institutional Quality in Determining the R&D Investment of Chinese Firms - Zhou, Yixiao (Wiley-Blackwell, 2014)
This study adds to the understanding of China's innovation prospects by examining how variations in institutional quality within China impact on the R&D efforts of firms located in different provincial regions. In the process of identifying the effect of institutional quality, the roles of other factors such as ownership types and market structures are revealed, which provides interesting insight into firms' R&D behavior. The key findings suggest that institutional quality positively affects the decision of firms to engage in R&D activities. Once firms start to engage in R&D, the subsequent expansion of firm-level R&D intensity depends on factors such as market structure. Therefore, strengthening domestic institutional quality is the first critical step towards the goal of building a knowledge-intensive economy in China. Efforts to nurture market development are also important for achieving this goal.